KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMA DENGAN TEAM TEACHING PADA PELAKSANAAN PROGRAM PENGENALAN LAPANGAN TAHUN 2015 - Rijanto, Marchasan Lexbin E Judah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This study aims to analyze the success of achieving learning goals that students or practice accomplish in carrying out their duties during the implementation of the field recognition program or PPL becomes important, at least by looking at students' hard skills with operational indicators achieved by students after learning, whatever treatment is used including when the team teaching is one alternative that must be used. The method used is a quasi experiment with research samples in MA Lepessa Cililin, it is important to see whether the team teaching that is imposed on students in class X and class XI in this case the subject, is an ideal condition for the achievement of the intended goals. With a test instrument that measures students 'mathematical understanding abilities and questionnaires to find out the tendency of students' attitudes towards mathematics and teachers, also pay attention to the control class, then analyzed by two-difference test and linear regression it can be concluded that learning by team teaching in the implementation of PPL of students in Education study programs mathematics in higher education units can be an alternative treatment, with more attention should be given to the supervisor and teacher tutor to each practitioner.